Toothpaste ingestion—evaluating the problem and ensuring safety: systematic review and meta-analysis - Petrović, Bojan; Kojić, Sanja; Milić, Lazar; Luzio, Alessandro; Perić, Tamara; Marković, Evgenija; Stojanović, Goran M. (Frontiers in Public Health, 2023)
This systematic review and meta-analysis aimed to evaluate the ingestion of toothpaste and its sequelae. The study adhered to the PRISMA guidelines and was registered in the PROSPERO database. A comprehensive search strategy was conducted across multiple databases, resulting in the inclusion of 18 relevant publications. Eligible studies encompassed various designs and included both children and adults as the study population. Data extraction was carried out systematically, and relevant information on study characteristics, interventions, and outcomes were collected. The assessment of bias was performed using the Joanna Briggs Institute’s Critical Appraisal Tools showing variations of bias among the included studies. The overall risk of systemic toxicity was found to be low, and no severe or life-threatening events were reported in the included studies. Furthermore, some toothpaste formulations containing higher concentrations of fluoride were associated with an increased risk of dental fluorosis. These findings have several implications for practice and policy. Healthcare providers and dental professionals should emphasize the importance of promoting safe toothpaste use, especially in vulnerable populations such as young children who are more prone to accidental ingestion. Public health campaigns and educational initiatives should aim to raise awareness about appropriate toothpaste usage and the potential risks. In addition, toothpaste manufacturers and regulatory bodies should consider revising guidelines and regulations to ensure the safety of oral care products, including the appropriate concentration of active ingredients. Future research should focus on investigating the long-term effects of toothpaste ingestion, exploring potential interactions between different active ingredients, and evaluating the efficacy of current preventive measures.